The COVID-19 pandemic and international students: Consequences for researchers, stakeholders and policymakers in the mobility field - Cairns, D.; França, T.; Calvo, D. M.; Azevedo, L. F. de (Evidence-based approach in Erasmus+. Warsaw seminar 2020, 2021)
Since the early months of 2020, COVID-19 has had a profound impact on societies, transforming social, economic and political life throughout the European Union. This resulted in dramatic change in a central aspect of life for many Europeans: the freedom to circulate between countries for non-essential purposes, including tertiary education. This loss has created problems for EU citizens and others from third-party countries, who have found themselves cut off from essential support or the means to return home in a safe and timely manner. In this chapter, we take a look at this situation, with our research questions considering some of the most prominent impacts of the pandemic on internationalised learning for both intra-EU exchange students and extra-EU educational migrants. To illustrate the emerging challenges, we have conducted research with international students in Portugal during the initial months of the public health emergency, from which we were able to identify issues that may be of concern to researchers, stakeholders and policymakers in the mobility field.